Depression and attempted suicide under pregabalin therapy - Kustermann, Andreas; Möbius, Cornelia; Oberstein, Timo; Mueller, Helge H.; Kornhuber, Johannes (Annals of General Psychiatry, 2014)
Originally developed for the treatment of epilepsy, pregabalin has become a compound with a wide spectrum of indications comprising anxiety disorders and chronic pain and is therefore largely prescribed. Thus, it is important for clinicians to be aware of rare, but serious adverse effects. The following report illustrates the case of a 20-year-old male with a severe depressive syndrome following pregabalin medication which even led to a suicide attempt.
EVALuna2:22329